2013
DOI: 10.1007/s10916-012-9895-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Widespread Adoption of Health Data Standards: An Exploratory Qualitative Study in Tertiary Healthcare Organizations in Saudi Arabia

Abstract: Although health data standards are perceived to be the essential solution for interoperability barriers within medical IT systems, the level of adoption of those standards still remains frustratingly low. Little is known about the barriers facing their adoption within the healthcare organizations context. In addressing this gap in the literature, based on IT related standards adoption theories such as Diffusion of Innovation Theory and the theories surrounding the Economics of Standards, a qualitative multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Technology readiness could be an enabler factor of the decision of Cloud Computing adoption [44]. Issues connected with existing infrastructure can have a negative impact on the adoption of Cloud Computing, as outlined by a study on the adoption of health data standards in Saudi Arabia [3]. However, Cloud Computing can help in solving the problem of the availability of IT resources [8].…”
Section: Technology Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology readiness could be an enabler factor of the decision of Cloud Computing adoption [44]. Issues connected with existing infrastructure can have a negative impact on the adoption of Cloud Computing, as outlined by a study on the adoption of health data standards in Saudi Arabia [3]. However, Cloud Computing can help in solving the problem of the availability of IT resources [8].…”
Section: Technology Contextmentioning
confidence: 99%
“…The shortage of health informatics specialists and IT professionals is another obstacle to e-health projects [2]. The implementation of e-health solutions may also encounter technical difficulties such as complexity, compatibility and insufficient IT infrastructure [3]. Despite these barriers, Saudi healthcare facilities have demonstrated a willingness to implement and improve their e-health services.…”
Section: Introductionmentioning
confidence: 99%
“…According to Anderson et al [13] since physicians are the main front line users of HIS, their resistance is one of the important factors affecting implementation of this system. Other researches [12,10,14,15] addressing failure factors showed that obstacles such as time constraints, security and privacy risk, lack of an adequate policy regarding medical IT, non-applicability with regard to patient characteristics, and complex clinical settings are among culprits. Similarly, lack of financial resources and high costs; poor management and bureaucracy; poor staff IT competency; lack of qualified IT personnel and lack of awareness of HIT (health information technology) values, are barriers to the adoption of health information technology in Arab countries' hospitals [16].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range distribution of health information systems is expected to receive extensive investigations with respect to its assessment, application and adoption. Besides, financial aspect is a key factor should always be considered seriously while assessing a health information system [1], because 10% -15% of governments' annual health budget can be saved by adopting the HIS [2]. Recently the research focused on the usability of HIS from users' point of view such as doctors, nurses, technicians or even patient [3].…”
mentioning
confidence: 99%